Aerobic capacity during cardiopulmonary exercise testing and survival with and without liver transplantation for patients with chronic liver disease. Issue 1 (29th November 2013) - Bernal, William; Martin‐Mateos, Rosa; Lipcsey, Miklós; Tallis, Caroline; Woodsford, Kyne; Mcphail, Mark J.; Willars, Christopher; Auzinger, Georg; Sizer, Elizabeth; Heneghan, Michael; Cottam, Simon; Heaton, Nigel; et al.
Abstract : Chronic liver disease (CLD) is associated with muscle wasting, reduced exercise tolerance and aerobic capacity (AC). Measures of AC determined with cardiopulmonary exercise testing (CPET) may predict survival after liver transplantation (LT), but the relationship with nontransplant outcomes is uncertain. In patients assessed for LT, we examined the relationship of CPET AC parameters with the severity of liver disease, nutritional state, and survival with and without LT. Patients assessed for elective first LT who underwent CPET and an anthropometric assessment at a single center were studied. CPET‐derived measures of AC that were evaluated included the peak oxygen consumption (VO2 peak) and the anaerobic threshold (AT). Three hundred ninety‐nine patients underwent CPET, and 223 underwent LT; 45% of the patients had a VO2 peak < 50% of the predicted value, and 31% had an AT < 9 mL/kg/minute. The VO2 peak and AT values correlated with the Model for End‐Stage Liver Disease score, but they more closely correlated with serum sodium and albumin levels. The handgrip strength correlated strongly with the VO2 peak. Patients with impaired AC had prolonged hospitalization after LT, and nonsurvivors had lower AT values than survivors 1 year after transplantation ( P < 0.05); this was significant in a multivariate analysis. One hundred seventy‐six patients did not undergo LT; the 1‐year mortality rate was 34.6%. The AT ( P < 0.05) and VO2 peak values ( P < 0.001) were lower for nonsurvivors. In a multivariate analysis, AT was independently associated with nonsurvival. In conclusion, AC was markedly impaired in many patients with CLD. In patients who did not undergo transplantation, impaired AT was predictive of mortality, and in patients undergoing LT, it was related to postoperative hospitalization and survival. AC should be evaluated as a modifiable factor for improving patient survival whether or not LT is anticipated. Liver Transpl 20:54–62, 2014 . © 2013 AASLD.